Green-reinforced Sedimentary Silt with Natural Curaua Fiber - Érico Rafael da Silva; Jair de Jesús Arrieta Baldovino; Ronaldo Luis Dos Santos Izzo (Journal of Natural Fibers, 2022)
Lime and cement as traditional binders need to be reduced in soil stabilization to avoid carbon dioxide emissions. Infrastructure development like paved structures, buildings, foundations, and dams involves exhaustive use of natural resources and serious concern for the environment. Using natural fibers as reinforced soil is a green-novel technique that improves soil properties such as strength, deformation, and expansion. Thus, this paper advances the performance of soil reinforcement using natural fiber. Natural Curauá fiber was used to improve unconfined compressive strength (qu), splitting tensile strength (qt), shear direct, and deformation of sedimentary silt in southern Brazil. By studying strength properties, 0.50% fiber and a length of 6 mm were selected as an optimum percentage and optimum length, respectively. For direct shear tests, the increase in strength at low confining stresses is proportional to the increase in fiber content and fiber length. By natural biodegradation of fiber, expanded polystyrene (EPS)-based treatment was employed, influencing a reduction of 10% in water absorption of fiber and increasing fiber’s tensile strength by 5%. Finally, the results demonstrate that natural fiber is a friendly-environmental alternative to enhance soil properties by applying rammed earth and some short-use earthworks in green constructions.